2015
DOI: 10.1007/s10967-015-4582-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of organic solvent radical cations in separations ligand degradation

Abstract: The dodecane radical cation reaction rate constant with CMPO was measured using ps electron pulse radiolysis/ absorption spectroscopy as k = (1.30 ± 0.11) 9 10 10 M -1 s -1 in dodecane/0.10 M CH 2 Cl 2 solution. No reactivity increase occurred when these solutions were pre-contacted with nitric acid, similar to the behavior observed for TODGA. To corroborate these kinetic data with steady-state radiolysis measurements, where acid pre-contacted CMPO showed significantly less degradation, it is proposed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…53,54,56 Other DGA degradation mechanisms suggest solvent radical cations as the ones which transfer an electron or a hydrogen atom (Hc) to the DGA, which causes it to become unstable and further degrade. 70,71 DC IV and DC V are products of the C amide -C ether bond breaking. Their intensities increase with increasing absorbed dose.…”
Section: Identication Of Degradation Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…53,54,56 Other DGA degradation mechanisms suggest solvent radical cations as the ones which transfer an electron or a hydrogen atom (Hc) to the DGA, which causes it to become unstable and further degrade. 70,71 DC IV and DC V are products of the C amide -C ether bond breaking. Their intensities increase with increasing absorbed dose.…”
Section: Identication Of Degradation Compoundsmentioning
confidence: 99%
“…The reaction rate constants computed by Mezyk et al imply the importance of reactions with the solvent radical cations in the case of TODGA. 70,71 We thus computed the radical Fukui function of mTDDGA, as it is an excellent indicator for reactivity towards radicals. 53,55 It provides highly valuable information, since during irradiation many radical species are produced in the considered organic phases.…”
Section: Calculation Of the Radical Fukui Functionmentioning
confidence: 99%
“…However, studies on radiolysis of TODGA have shown that its degradation is dominated by reactions with radical cations of the diluent. [7][8] For the comparison of the radiolytic degradation of different ligands or to study the effect of changing the diluent, dose constants (d) are being used in this research. [9] The dose constant is determined by the slope of the linear fit of the natural logarithm of the concentration of the molecule as a function of the absorbed dose.…”
Section: Introductionmentioning
confidence: 99%
“…Radical cations produced in the irradiated alkane diluent have been implicated as the reactive species that initiate lipophilic DGA degradation. [10,11] We are not aware of previous work that investigates the radiation chemistry of DGAs in aqueous solution. The aqueous matrix gives rise to a completely different set of reactive species than does the organic phase when irradiated and therefore it was deemed interesting to measure the rates of degradation and identify the products of the radiolysis of hydrophilic DGAs and compare them to previous organic-phase work.…”
Section: Introductionmentioning
confidence: 99%